2003
DOI: 10.1109/tap.2003.818008
|View full text |Cite
|
Sign up to set email alerts
|

Measurements and analysis of the indoor wideband millimeter wave wireless radio channel and frequency diversity characterization

Abstract: This paper presents results of frequency domain measurements conducted to evaluate the effectiveness of frequency diversity in mitigating the effects of multipath fading in indoor microcellular channels employing omni-directional receive antenna in the band 63.4-65.4 GHz. The performance of frequency diversity for 155 MHz and other channel bandwidths to accommodate modulated signals with data rates up to 155 Mb/s is presented. Results are obtained using maximum selection combining and presented as functions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…In terms of the channel model we use, while our diffraction model is based on fundamental physics, we are motivated by the extensive body of knowledge on mm wave propagation measurement and modeling. Measurement campaigns in indoor environments include [20]- [29]. For typical indoor environments with omnidirectional antennas, specular reflections from surfaces are dominant contributors to the received signal power as compared with diffraction or scattering [24], [30]- [32].…”
mentioning
confidence: 99%
“…In terms of the channel model we use, while our diffraction model is based on fundamental physics, we are motivated by the extensive body of knowledge on mm wave propagation measurement and modeling. Measurement campaigns in indoor environments include [20]- [29]. For typical indoor environments with omnidirectional antennas, specular reflections from surfaces are dominant contributors to the received signal power as compared with diffraction or scattering [24], [30]- [32].…”
mentioning
confidence: 99%
“…Figure 22 shows three CIR main components, namely a high gain path representing the LOS component and two other low gain NLOS spatial-clusters, where each spatialcluster has multiple time-clusters, since the different MPCs have different Time-of-Arrivals (ToA), as described by the n-th cluster delay τ n cl and the AoA characteristics. On the same note, the different measurements conducted at multiple mmWave frequency bands reported that the received PDPs and PAPs were detected in spatial-clusters and time-clusters [14], [44], [54], [69], [121], [225]. The concept of timeclusters and spatial-clusters was further extended in [72], [76], [79], [80], [105], [211], where multiple received components of a specific time-cluster were observed throughout multiple spatial-clusters, which are also referred to as spatial lobes.…”
Section: F the Wideband Channel Modelmentioning
confidence: 99%
“…The spatio-temporal characteristics of the 60 GHz channel were also studied in [14], [28], [66], [69], [120], [121], [125], [142], [166], [175], [206], where the model of the indoor 60 GHz channel is based on the TSV [67] and on the extended-SV [171], [172] channel models. The general double-directional wideband CIR is given by:…”
Section: As Ds θmentioning
confidence: 99%
“…The antennas were mounted on wooden tripods with a small section of metal behind the directional antennas, which does not influence the pattern. Calibration was performed in an anechoic chamber to compensate the frequency response of antennas and cables as suggested in [13]. These two measured bands were free from interference during the measurement campaign, as confirmed by measurements with a spectrum analyzer (PSA E4445A, Agilent, Santa Clara, CA, USA).…”
Section: Measurement Systemmentioning
confidence: 99%